Medetnični odnosi v slovenskem etničnem prostoru - Hafner-Fink, Mitja (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 1993)
The first part introduces some theoretical and methodological starting points for the research of interethnic relations. A thesis about comparative nature of research has been launched, at least as far as ethnicity is concerned. The second part of the article provides basic information on data collecting, sample and sample frame of the following research projects: Interethnic relations and national identity in the town of Szentgotthard. The third part presents the three groups of indices prepared within the framework of the research on the basis of survey of the data collected.
Keywords: etnična identiteta; etnični odnosi; Madžari; narodne manjšine; porabski Slovenci; Prekmurje; Slovenija